Pengaruh Kesadaran Wajib Pajak, Pengetahuan Perpajakan dan Penerapan Sistem e-Filling Terhadap Kepatuhan Wajib Pajak: Sosialisasi Perpajakan Sebagai Mediasi - Tiend J. L. Belo; Hyronimus Se; Laurentius D. Gadi Djou (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the influence of taxpayer awareness, tax knowledge, and the implementation of the e-Filing system on taxpayer compliance, with tax socialization as a mediating variable. The study sample consisted of 30 individual taxpayers using e-Filing in Ende Regency using a purposive sampling approach. The analysis technique used Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results show that tax knowledge has a positive and significant effect on taxpayer compliance. Conversely, taxpayer awareness and the implementation of the e-Filing system do not directly affect taxpayer compliance. Tax socialization also has no significant effect on taxpayer compliance and does not mediate the relationship between awareness, tax knowledge, and e-Filing implementation on taxpayer compliance. These findings emphasize the importance of improving tax literacy as a key factor in improving taxpayer compliance.